Concealment of Chaos Time-Delay Signature Through Phase-Conjugate Feedback and Chaos Optical Injection - Penghua Mu; Wei Pan; Lianshan Yan; Bin Luo; Xihua Zou (IEEE Photonics Journal)
In this paper, we numerically demonstrate that the concealment of time-delay signature (TDS) can be readily achieved via the combined mechanism of phase-conjugate feedback (PCF) and chaotic optical injection. To show the potential advantages of the proposed scheme, its counterpart, i.e., a slave semiconductor laser (SSL) subjected to chaotic optical injection from a master semiconductor laser (MSL) with conventional optical feedback (COF) is studied in parallel. In particular, we consider a fair situation where the MSL in both PCF and COF shows a comparable peak value in the autocorrelation function computed from the intensity time series. Our simulations uncover that combining the mechanism of PCF and chaotic optical injection is beneficial for TDS concealment in the SSL. To better understand this, the effects of some control parameters including injection and feedback are comparably studied. The results further prove that, as the injection or feedback parameters are varied, the proposed PCF-system always exhibits weaker autocorrelation around the feedback delay value when compared to the COF-system. In the meantime, the former system allows for larger bandwidth and, thus, paves way for important applications to secure communication and random-number generation.